2003
DOI: 10.1099/mic.0.26155-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of a strict anaerobe to oxygen: survival strategies in Desulfovibrio gigas

Abstract: The biochemical response to oxygen of the strictly anaerobic sulfate-reducing bacterium Desulfovibrio gigas was studied with the goal of elucidating survival strategies in oxic environments. Cultures of D. gigas on medium containing lactate and sulfate were exposed to oxygen (concentration 5-120 mM). Growth was fully inhibited by oxygen, but the cultures resumed growth as soon as they were shifted back to anoxic conditions. Following 24 h exposure to oxygen the growth rate was as high as 70 % of the growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 48 publications
5
41
0
6
Order By: Relevance
“…SRB might have developed adaptation strategies to protect them against oxygen, including oxygen removal. The ability to reduce oxygen is widespread among SRB (Dannenberg et al, 1992;Fareleira et al, 2003;Fournier et al, 2006;Fröhlich et al, 1999;Kjeldsen et al, 2005;Kuhnigk et al, 1996;Mukhopadhyay et al, 2007;Sass et al, 2002;Sigalevich & Cohen, 2000). However, oxygen reduction by SRB seems to be a protective mechanism against the harmful effects of oxygen rather than an energycoupled conservation mechanism to allow growth.…”
Section: Introductionmentioning
confidence: 99%
“…SRB might have developed adaptation strategies to protect them against oxygen, including oxygen removal. The ability to reduce oxygen is widespread among SRB (Dannenberg et al, 1992;Fareleira et al, 2003;Fournier et al, 2006;Fröhlich et al, 1999;Kjeldsen et al, 2005;Kuhnigk et al, 1996;Mukhopadhyay et al, 2007;Sass et al, 2002;Sigalevich & Cohen, 2000). However, oxygen reduction by SRB seems to be a protective mechanism against the harmful effects of oxygen rather than an energycoupled conservation mechanism to allow growth.…”
Section: Introductionmentioning
confidence: 99%
“…A central iron, coordinated by four cysteines, constitutes the redox-active site alternating between ϩ2 and ϩ3 oxidation states. Rdxs are crucial for oxidative stress responses in anaerobic organisms by rapidly transferring metabolic reducing equivalents to superoxide reductases or rubredoxin:oxygen oxidoreductases to reduce oxygen or reactive oxygen species (11,12). The link to general metabolism is provided by NAD(P)H and NAD(P)H:RdxRs (11,13,14).…”
mentioning
confidence: 99%
“…However, a growing number of studies have demonstrated that some SRB can tolerate a certain degree of DO (Abdollahi and Wimpenny, 1990;Cypionka et al, 1985;Fareleira et al, 2003;Mogensen et al, 2005). Consistently, no significant differences in the abundance of dsrA/B genes were observed between S1, S2 and S3, indicating that low levels of DO had less effect on SRB in the bioreactor.…”
Section: Discussionmentioning
confidence: 68%